Analysis of Technology Based Teaching Materials in Improving Teacher Performance at MAN Insan Cendekia Central Bengkulu - Lisa Wulandari; Roza Evalia; Tisa Distiana (Al-Khair Journal: Management Education, 2026)
Abstract: The analysis of technology-based teaching materials in improving teacher performance is still an important issue in the digital era, especially in educational units that seek to integrate technology in the learning process. This study aims to describe and analyze technology-based teaching materials in improving the performance of English teachers at MAN Insan Cendekia Central Bengkulu. The research uses a descriptive qualitative method with data collection techniques through observation, in-depth interviews, and documentation. The research informants included madrasah heads, curriculum waka, teachers, and students, with data analysis using the Miles and Huberman models and triangulation to ensure the validity of the data. The results of the study show that technology-based teaching materials have been applied through systematic planning, implementation, and evaluation stages, including the use of e-modules, learning videos, LMS, interactive media, and digital application-based evaluations. The implementation contributes to improving teachers' pedagogic, professional, social, and personality competencies so that teacher performance becomes more innovative and adaptive to the demands of digital learning. However, there are still obstacles in the form of limited infrastructure and the need for continuous training. Therefore, strengthening madrasah policies, improving infrastructure, and sustainable professional development are needed to optimize technology integration in improving teacher performance in a sustainable manner.Keywords: Teaching Material Analysis, Technology-Based, Teacher Performance. Abstrak: Analisis bahan ajar berbasis teknologi dalam meningkatkan kinerja guru masih menjadi isu penting di era digital, terutama di satuan pendidikan yang berupaya mengintegrasikan teknologi dalam proses pembelajaran. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis bahan ajar berbasis teknologi dalam meningkatkan kinerja guru Bahasa Inggris di MAN Insan Cendekia Central Bengkulu. Penelitian ini menggunakan metode kualitatif deskriptif dengan teknik pengumpulan data melalui observasi, wawancara mendalam, dan dokumentasi. Informan penelitian meliputi kepala madrasah, waka kurikulum, guru, dan siswa, dengan analisis data menggunakan model Miles dan Huberman serta triangulasi untuk memastikan validitas data. Hasil penelitian menunjukkan bahwa bahan ajar berbasis teknologi telah diterapkan melalui tahapan perencanaan, implementasi, dan evaluasi yang sistematis, termasuk penggunaan e-modul, video pembelajaran, LMS, media interaktif, dan evaluasi berbasis aplikasi digital. Implementasi tersebut berkontribusi pada peningkatan kompetensi pedagogis, profesional, sosial, dan kepribadian guru sehingga kinerja guru menjadi lebih inovatif dan adaptif terhadap tuntutan pembelajaran digital. Namun, masih terdapat kendala berupa keterbatasan infrastruktur dan kebutuhan akan pelatihan berkelanjutan. Oleh karena itu, penguatan kebijakan madrasah, peningkatan infrastruktur, dan pengembangan profesional berkelanjutan diperlukan untuk mengoptimalkan integrasi teknologi dalam meningkatkan kinerja guru secara berkelanjutan.Kata kunci: Analisis Materi Ajar, Berbasis Teknologi, Kinerja Guru.